Feasibility of Power Control for Multi-Channel User in Inter-Femtocell Network - Anggun Fitrian Isnawati; Risanuri Hidayat; Selo Sulistyo; I Wayan Mustika (Institute of Advanced Engineering and Science, 2016)
The importance of power control feasibility is closely related to the direct implementation of the system, which is related to interference between users in the femtocell network and also related to the optimal use of power transmit that can create a long-lasting battery. Implementation of the feasibility of power control in this study is focused on the centralized femtocell network with a multi-channel user. The research method in this study is based on the use of feasible solution algorithms in power control by observing the output of power vector that should be valued non-negative, which means that it can be implemented. This result indicates that all of user can reach the specified target SINR. SINR users will increase when there are additional channels for user groups. The average power of user will also decrease while increasing the amount of provided channels. The greater number of users in a user group, the less value SINR can be obtained